ANALISIS PENGARUH IPM, PENGANGGURAN, DAN PDRB TERHADAP KEMISKINAN DI PROVINSI SUMATERA UTARA TAHUN 2017-2021 - Muhammad Ramadhan Zulfi; Masruri Muchtar; Pardomuan Robinson Sihombing (Jurnal Ekonomi dan Bisnis, 2023)
his research aims to determine the effect of the human development index, open unemployment rate and economic growth on the poverty rate in North Sumatra Province. This study uses secondary data from districts/cities in North Sumatra Province in a span of 5 years from 2017 to 2021. The research was conducted using panel data regression with a random effect model. Based on the research results, it was found that the three independent variables simultaneously influenced the dependent variable. Partially, the HDI variable has a negative and significant effect on the poverty rate in North Sumatra Province. The open unemployment rate variable has a positive and significant effect on the poverty rate. However, the economic growth variable has a positive and significant effect on the poverty rate. HDI has the biggest influence compared to the other two variables. The government can encourage increasing the HDI of its people to reduce poverty. In addition, the government must also reduce unemployment rate and carry out economic equity to reduce poverty.Keywords: economic growth, human development index, poverty, unemployment